China's Model of Free Economic Zones: Experiences and Prospects after over 20 Years - Meng, Guangwen (Mongolian Journal of International Affairs, 2013)
It is true that no FEZs in the world like in China have made so strong impact on national economic development and reform. Their existing condition, however, has been changed since the middle 1990s. Chinese FEZs have to face the new challenges and problems. This study discussed and prospected the transformation and further development of Chinese FEZs in the 21st century as well as their significance for the transformation of FEZs in other country based on the analyzing of the indicators such as the role, policy, industrial sectors, administration, development model, spatial structure, and location in this study. DOI: http://dx.doi.org/10.5564/mjia.v0i12.95 Mongolian Journal of International Affairs No.12 2005: 65-82